Injectable Iron and Blood Transfusion for Correction of Anemia in Pregnancy in a Peripheral Tertiary Hospital in Bangladesh: A Quasi-Experimental Study - Billah, Syed Muhammad Baqui; Naher, Fatema Kamrun (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Anemia in pregnancy is one of the most commonly encountered medical disorders. Objective: To compare the effects of injectable iron and blood transfusion for correction of anemia in pregnancy. Methods: This quasi-experimental study was conducted in the Obstetrics & Gynaecology outpatient department (OPD) of Shaheed Ziaur Rahman Medical College Hospital, Bogura, Bangladesh, between April and December of 2020on 100 expecting mothers through interviews, investigation of hemoglobin (Hb) level at 16 weeks, 24-28 weeks and 36 weeks. The injectable iron and blood transfusion were the experiments given to the pregnant women around 24-28 weeks.The effect of the experiment along with other factors were assessed over the change of Hb level from 24-28 weeks to 36 weeks. Results: Only iron injection singly significantly improved Hb level (1.4 mg/ dl, p<0.001) though it improved a little in combination with blood transfusion (0.472 mg/ dl, p=0.15) too, but blood alone was associated with decreased Hb level (-0.414 mg/dl, p=0.07). Other factors were not related to the change. Conclusion: Iron injection improves hemoglobin status and should be given to all anemic women irrespective of presence or absence or other risk factors. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 372-376